(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
Stimuli-responsive nanoparticles (SRNs) provide an innovative method in pharmaceuticals, facilitating accurate, on-demand drug release systems customized for particular therapeutic requirements. These sophisticated materials react to internal (pH, enzymes, and redox potential) or exterior (temperature, light, and magnetic fields) stimuli, enabling regulated drug release while reducing adverse effects. Recent developments in the design and engineering of SRNs have improved their sensitivity, biocompatibility, and drug-loading efficiency, rendering them optimal candidates for customized therapy. Notwithstanding their potential, issues related to stability, possible cytotoxicity, and scalability impede their clinical application. Contemporary research emphasizes surmounting these obstacles using multistimuli-responsive systems and the use of developing technologies such as artificial intelligence. This review elucidates the processes, material developments, and pharmacological applications of SRNs, addresses significant limits, and examines prospective avenues for their advancement. By tackling these issues, SRNs possess the capacity to revolutionize contemporary drug delivery methods, providing unparalleled precision and efficiency in therapeutic treatments.